Using complementary NMR data sets to detect inconsistencies and model flaws in the structure determination of human interleukin-4 - Smith, LJ; van Gunsteren, WF; Hansen, N (American Chemical Society, 2017)
The derivation of protein structure from values of observable quantities measured in NMR experiments is a rather non-trivial task due to (i) the limited number of data compared to degrees of freedom of a protein, (ii) the uncertainty inherent to the function connecting an observable quantity to molecular structure, (iii) the finite quality of biomolecular models and force fields used in structure refinement, and (iv) the conformational freedom of a protein in aqueous solution, which requires extensive conformational sampling and appropriate conformational averaging when calculating or restraining to sets of NMR data. The protein interleukin-4 (IL-4) has been taken as a test case using NOE distances, S2 order-parameters and 3J-couplings as test data and the former two types of data as restraints. It is shown that by combining sets of different, complementary NMR data as restraints in MD simulation inconsistencies in the data or flaws in the model and procedures used to derive protein structure from NMR data can be detected. This leads to an improved structural interpretation of such data particularly in more mobile loop regions.